Lumio media development to improve motivation and critical thinking abilities in elementary school students - Anjarweni, Bondhaningtyas; Buchori, Achmad; Sulianto, Joko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Science learning in elementary schools is faced with the challenge of conventional media, which results in low motivation and critical thinking skills of students. This study aims to develop Lumio by SMART media through the STEAM approach on the metamorphosis of living things material in elementary schools. This study uses an R&D approach with the MDLC development model. Participants in this study included teachers and 18 third-grade students of SDN Sudo. Data collection methods included observation, interviews, questionnaires, pre-tests, and post-tests. Data were analyzed qualitatively and quantitatively to assess the feasibility of the product. The results of the validity test from the media validator obtained scores of 94% and 98% with a very valid category. The validity test of the material obtained results of 94% and 96%, in the very valid category. The results of the student and teacher questionnaires also showed positive results, namely 94% and 91% with a very good category, thus indicating that this media is feasible and effective to use. The results of the paired sample T-test, with N-Gain values of 0.86 and 0.68, respectively, showed differences and improvements in student learning outcomes. As a follow-up, Lumio by Smart Media is expected to be used to enhance students' learning experiences. Lumio by SMART Media, with its STEAM approach, is recommended for continuous implementation in elementary school science curricula as a concrete solution to improve educational quality, student motivation, and critical thinking skills. It also serves as a reference for teachers and schools in optimizing the use of innovative learning technologies.